Seychelles : Third Review under the Extended Arrangement, Request for Modification of Performance Criteria, Financing Assurances Review; Staff Report; Press Release on the Executive Board Discussion. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2011)
Seychelles's economy has recovered strongly from the debt crisis and global recession, owing to high foreign direct investment and a rebound in tourism. Inflation remained near zero, and the country continued to rebuild its international reserves and reduce public debt. In 2011, the policy mix under the economic program supported by the Extended Fund Facility has been adjusted in response to global commodity price shocks and financial difficulties of Air Seychelles. Structural reforms will focus on strengthening the financial sector and restructuring of state-owned financial institutions.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet